Effect of cockle shell as coarse aggregates replacement on mechanical properties of concrete / Nor Maizatul Akmar Addnan ... [et al.] - Addnan, Nor Maizatul Akmar; Zuhan, Nurizaty; A. Mujedu, Kasali; Kado, Bishir (2024)
Gravel is a natural raw material used in concrete mixtures. However, more of this scarce resource was used, which reduced the amount of gravel-based coarse aggregates that could be produced. As a result, efforts to preserve natural coarse aggregates for future generations were critical. So, an innovation to replace this natural coarse aggregate was required. The dumping of cockle shell waste by the cockle trade emits a stinking smell and pollutes the environment. This study investigates the density, compressive, splitting tensile and flexural strengths of concrete containing cockle shell as a coarse aggregate substitute. Four concrete mixes were prepared by integrating diverse contents of cockle shell as 0%, 10%, 20% and 30% partial replacement of coarse aggregates by weight of gravel. Concrete becomes less dense as a large amount of cockle shell is integrated. Utilization of cockle shell up to 10% enhances the compressive strength of concrete. However, increasing the amount of cockle shell by up to 30% can improve the splitting tensile and flexural strength of concrete.